Strategic change management : case study of National Semiconductor Corporation - Rahamat Bidin (2009)
A long established semiconductor company has just embarked on a strategic change process. The company has successfully concluded the first phase of its transformation from a troubled to a viable company and is now at the onset of its second phase to transform it into a great company. The company adopted the fundamental change strategy and uses the 7S framework to manage the change process. The case study focused on the methodology and the tools used by the company to successfully manage the change.